2022
DOI: 10.1002/cam4.4947
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of curability expectations in patients with gastrointestinal cancers

Abstract: Background Assessment of illness and treatment understanding among cancer patients has largely focused on those with advanced disease. Less is known about patient expectations at earlier stages of cancer and potential modifiers of accurate understanding. Methods We assessed accuracy of cure expectations in patients across all stages with gastrointestinal (GI) cancers. Accuracy was determined by independent reviews of patient health records by oncologists on the investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…This proportion of change from accurate to less accurate beliefs is similar to that reported in recent longitudinal examinations of prognostic beliefs. 25,33,34 We found that on average, 7.1% of patients changed to inaccurate belief and 14.3% changed to uncertain belief at each time point. Previous studies have reported that between 8% and 20% of patients change from an accurate to an inaccurate belief between surveys.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This proportion of change from accurate to less accurate beliefs is similar to that reported in recent longitudinal examinations of prognostic beliefs. 25,33,34 We found that on average, 7.1% of patients changed to inaccurate belief and 14.3% changed to uncertain belief at each time point. Previous studies have reported that between 8% and 20% of patients change from an accurate to an inaccurate belief between surveys.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have reported that between 8% and 20% of patients change from an accurate to an inaccurate belief between surveys. 25,33,34 The slightly lower proportion of change to inaccurate beliefs in our sample may be explained by the longer time period under analysis, as the sample evolves to a majority of accurate beliefs over time. Alternately, it may be that these changes are captured as "change to uncertain" observations instead, allowing us to discern that even when patients change to less accurate beliefs, they appear to do so hesitantly.…”
Section: Discussionmentioning
confidence: 82%
“…We have pilot tested a portal-enabled approach called “PERSON” ( P atient portals to E licit essential patient- R eported elements of communication S upporting person-centered ON cologic care) 21 , 22 in a sample of gastrointestinal (GI) oncology clinics within our comprehensive cancer center to elicit information about personhood, ITU, and HRV (hereafter, “the questionnaire” refers to the combined ITU and HRV questionnaire items elicited through the portal). 23 , 24 This pilot work provided evidence of feasibility and acceptability, while also showing an association between the PERSON approach and higher patient ratings of clinicians' communication quality. 21 , 22 In the present study, we explored the perspectives of patients and clinicians who participated in the pilot study for additional feedback about workflow considerations, processes, and portal use related to PERSON.…”
Section: Introductionmentioning
confidence: 77%
“…The communication between oncologists and patients plays a crucial role in how curability is perceived [9,10]. Oncologists must provide clear and accurate information regarding diagnosis, prognosis, and treatment options, while patients need to understand the given information from their oncologists and adhere to the opportunity to express their concerns and doubts about the treatment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Oncologists must provide clear and accurate information regarding diagnosis, prognosis, and treatment options, while patients need to understand the given information from their oncologists and adhere to the opportunity to express their concerns and doubts about the treatment [10,11]. For a better understanding of the goals of cancer treatment, it is essential to ensure informed consent and facilitate medical decision-making that aligns with the individual needs of each patient [9,12]. Although, communicating a prognosis can be distressing [13,14], effective communication from clinicians to patients can encourage patients to integrate realistic information about the possibility of a cure without losing hope, while maintaining their psychological well-being at the same time [8,15,16].…”
Section: Introductionmentioning
confidence: 99%